Preliminary tsunami analytical fragility functions proposal for Italian coastal residential masonry buildings. (June 2021) - Belliazzi, Stefano; Lignola, Gian Piero; Di Ludovico, Marco; Prota, Andrea
Abstract: Scientific community showed particular interest in tsunami risk assessment in the last years due to several worldwide tsunami events where high damages and human casualties were recorded during post-event surveys. This paper investigates the behaviour of Italian coastal residential masonry buildings under tsunami loads. Main fragility curves available in literature are based on empirical databases and consequentially, the structural behaviour is strictly related to local building typologies of other countries. For masonry buildings, it is complex to predict global response due to high material inhomogeneity, especially in the case of regional scale analysis; a critical review on local mechanisms activation of masonry walls under tsunami loads is briefly performed. Therefore, local mechanisms activation for masonry walls are investigated depending on out-of-plane and in-plane mechanisms assuming flexural and shear failure. Structures designed for gravity or seismic loads are generated based on several building classes depending on number of storeys and age of construction. Monte Carlo analyses generated building models for each identified building class to simulate the behaviour of Italian masonry buildings. Preliminary analytical tsunami fragility curves are developed in order to assess the vulnerability of Italian coastal residential masonry buildings under tsunami loads. A critical review is proposed on developed fragility curves.